Analisis Determinan Likuiditas pada PT. Garuda Indonesia Tbk: Studi Empiris Periode 2014-2023 - Ramdhani, Faiha Tiara; Wardhani, Nurhastuty Kesumo (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study aims to identify and discuss the effect of accounts receivable turnover, working capital turnover, revenue growth, and inventory turnover on the liquidity level of PT Garuda Indonesia Tbk during the 2014–2023 period. This research uses a descriptive quantitative approach, with data collected through documentation methods, including literature exploration, library studies, financial reports, company documents, and supporting articles relevant to the research object. The data were analyzed using multiple linear regression, an analytical model involving one dependent variable and two or more independent variables to determine the relationship and magnitude of influence among variables. The results show an R-Square value of 89.7%, meaning that accounts receivable turnover, working capital turnover, revenue growth, and inventory turnover explain 89.7% of the variation in liquidity, while the remaining percentage is influenced by other factors outside the research model. The t-test results indicate that only working capital turnover has a significant effect on liquidity, while the other variables do not show a significant partial effect. Meanwhile, the F-test results prove that all independent variables simultaneously have a positive and significant effect on the liquidity of PT Garuda Indonesia Tbk during the study period. These findings emphasize the importance of effective working capital management in maintaining the company’s ability to meet short-term obligations amid dynamic airline financial performance in a consistent, measurable, and sustainable manner.